Reverberations of extramural experiences in Dentistry teaching - Viana, Patricia Ferreira de Sousa; Adad, Shara Jane Holanda Costa; Pedrosa, José Ivo dos Santos (ABCS Health Sciences, 2015)
Introduction: A dentist’s profile, which is predominantly technical, results from a training focused on dental, cosmetics and decontextualized clinics. Hence, the Brazilian National Curriculum Guidelines arouse, comprising, among other recommendations, the expansion of teaching and learning spaces based on real settings of practice that enable concrete experiences in the social reality. Objective: To identify, in the pedagogical opportunities proposed for the course, aspects that may influence changes on the teaching‑learning process in Dentistry. Methods: This is a qualitative and descriptive study, based on socio‑poetics approach to produce and analyze data. Undergraduates in Dentistry inserted in extramural pedagogical activities took part in the study. Four socio‑poetics workshops were conducted, and they were used as an instrument to develop narratives on the teaching‑learning experiences. Results: Three lines of thought emerged from the socio‑poetics data analysis: time to live the teaching‑learning experiences; coexistence of old and new pedagogical approaches; and challenges arising from change projects. Conclusion: Despite the faced challenges, the importance of curricular or non‑curricular extramural is assumed in Dentistry teaching. These experiences lead students to share spaces of practices in the Brazilian Unified Health System with other actors; thus, by moving in the world of work and teaching, students create a mental model of the teaching‑learning process, which is influenced by the theoretical framework, by opportunities of experiences in the field of practice, and by personal interests. Such elements interfere and increase the perception of themselves and of the world, since they advance in the training process, building a singular way.